2011
DOI: 10.5732/cjc.010.10587
|View full text |Cite
|
Sign up to set email alerts
|

Association between p21 Ser31Arg polymorphism and cancer risk: a meta-analysis

Abstract: P21 (CDKN1A), a key cell cycle regulatory protein that governs cell cycle progression from G1 to S phase, can regulate cell proliferation, growth arrest, and apoptosis. The Ser31Arg polymorphism is located in the highly conserved region of p21 and may encode functionally distinct proteins. Although many epidemiological studies have been conducted to evaluate the association between the p21 Ser31Arg polymorphism and cancer risk, the findings remain conflicting. This meta-analysis with 33 077 cases and 45 013 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
6
0
1
Order By: Relevance
“…CDKN1A activity is regulated by p53 which binds to its promoter and induces cell cycle arrest in response to various stimuli . This gene is often deregulated in human cancers with altered expression reported in several cancers including cervical, breast, ovarian, liver, uterine, and head and neck cancers . The CDKN1A SNP (rs1801270) at codon 31 (Ser31Arg) reported in the present study falls in a highly conserved N‐terminal region of the protein, which is demonstrated to contain tumor suppressor function .…”
Section: Discussionmentioning
confidence: 58%
“…CDKN1A activity is regulated by p53 which binds to its promoter and induces cell cycle arrest in response to various stimuli . This gene is often deregulated in human cancers with altered expression reported in several cancers including cervical, breast, ovarian, liver, uterine, and head and neck cancers . The CDKN1A SNP (rs1801270) at codon 31 (Ser31Arg) reported in the present study falls in a highly conserved N‐terminal region of the protein, which is demonstrated to contain tumor suppressor function .…”
Section: Discussionmentioning
confidence: 58%
“…Epigenetically silencing through long non-coding RNAs happens frequently [149] and was recently detected in cholangiocarcinoma [150]. Additionally, diverse single nucleotide polymorphisms of p21 are reported to influence the risk of developing cancers including esophageal [151], colorectal and estrogen-related cancer [152], associated with a higher risk of second primary malignancies in head and neck carcinoma [153].…”
Section: Translating In Tumor Therapymentioning
confidence: 99%
“…The CDKN1A gene was initially considered as a potential tumor suppressor. However, studies have reported that this gene could act as an oncogene due to its anti-apoptotic activities 100 , 101 . It is involved in p53-mediated inhibition of cell proliferation in response to DNA damage leading to cell cycle arrest at the G1/S checkpoint 102 , 103 .…”
Section: Discussionmentioning
confidence: 99%